Race Pedagogy: Faculty Preparation Matters. Issue 4 (1st October 2016) - Williams, Stacy A. S.; Conyers, Addrain
ABSTRACT: This article addresses some of the concerns faculty have in managing a discussion on race in the classroom, by making explicit that which is often implicit when discussing race. Key objectives are to mitigate tension in the classroom, thereby creating a safe space for difficult race discussions, and to develop and promote faculty preparation for courses and course components that focus on race and racism. Development of pedagogical skills is a function of self-awareness, emotion management, and understanding student values. Faculty preparation needs to be ongoing, flexible, and adaptable to the values of the students and the system. Student-centered examples and strategies are provided to aid emotion management in the classroom.